KINERJA PEMERINTAH DESA DALAM PENYELENGGARAAN DIGITALISASI DESA DI DESA PETUMBUKAN KECAMATAN GALANG KABUPATEN DELI SERDANG - Pangaribuan, Nur Ajijah; Batubara, Beby Mashito; Deliana, Marlina (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This paper aims to see how village digitalization can accelerate village performance in Petumbukan village. The method used in this paper is a descriptive method with a qualitative approach. The results of this study indicate that the ongoing digitalization in Petumbukan village has a positive impact in terms of providing improvements to services to village communities.